Acceptance of a mHealth program for obesity prevention in adolescents: mixed sequential study - Sousa, Pedro Miguel Lopes de (2020)
Background: The health area has been adapting to the use of technology, using it as an important ally in programs for monitoring and preventing obesity and associated problems. Objective: To assess the acceptance of the TeenPower e-therapeutic program in adolescents. Methodology: Sequential mixed-method study with 47 students in grades 6, 7, and 8 in Portugal. In the first phase, data were collected through a questionnaire consisting of sociodemographic data, acceptance questionnaire, food choices, body image (dis)satisfaction, lifestyle profile, and eHealth literacy. The second phase included an interactive online session with a discussion forum, followed by Bardin's content analysis. Results: The acceptance of the TeenPower program by adolescents had a positive mean score in the 4 factors assessed on the scale. eHealth literacy was also positively associated with the perceived usefulness of the TeenPower program. Conclusion: The successful acceptance of e-therapeutic programs can lead to innovation and improvement in obesity prevention, thus providing an effective response to the adolescents' expectations and needs.